2010
DOI: 10.1029/2009jb006395
|View full text |Cite
|
Sign up to set email alerts
|

Compaction‐induced stress variations with depth in an active anticline: Northern Apennines, Italy

Abstract: [1] It is shown that the stress field can vary with depth, even within a homogeneous tectonic setting, as documented for the active Mirandola fault-related fold along the buried front of the northern Apennines. Analyses of borehole breakouts and other well data, integrated with seismological information and field evidence, show that extension perpendicular to the fold axis, above approximately 1200 m, changes to a strike-slip stress field and finally to compression near the main detachment at depth. Similar al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 108 publications
3
64
2
Order By: Relevance
“…Deep features revealed by our tomography complement results from seismic profiles (Pieri and Groppi, 1981;Picotti and Pazzaglia, 2008;Toscani et al, 2009b;Carminati et al, 2010;Fantoni and Franciosi, 2010;Boccaletti et al, 2011;Lavecchia et al, 2012;Bonini and Toscani, 2014) and geologic reconstructions (Burrato et al, 2003). The strong model complexity observed in the aftershocks volume, responsible for impressive hypocentral refinements of this study, is helpful, with the aftershock distribution itself, in defining the fault geometry.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Deep features revealed by our tomography complement results from seismic profiles (Pieri and Groppi, 1981;Picotti and Pazzaglia, 2008;Toscani et al, 2009b;Carminati et al, 2010;Fantoni and Franciosi, 2010;Boccaletti et al, 2011;Lavecchia et al, 2012;Bonini and Toscani, 2014) and geologic reconstructions (Burrato et al, 2003). The strong model complexity observed in the aftershocks volume, responsible for impressive hypocentral refinements of this study, is helpful, with the aftershock distribution itself, in defining the fault geometry.…”
Section: Discussionsupporting
confidence: 84%
“…The tip of the low-angle eastern segment struck by the Mw 6.0 May 20 event emerges close to middle thrust of the Ferrara thrust-fold system as defined by seismic reflection data (section B in Fig. 6; Carminati et al, 2010). In addition, relocated aftershocks of the May 20 main-shock preferentially cluster on the deeper, low-angle portion of the middle Ferrara thrust (section B in Fig.…”
Section: Geometry Of the Fault Systemmentioning
confidence: 92%
See 1 more Smart Citation
“…As the subduction hinge retreats toward the foreland, the subsidence rate increases subduction zones (e.g., Doglioni et al 1999) reveals the presence of an active accretionary wedge delimited at its footwall by the external thrust front and at its hangingwall by a thrust responsible for the rapid uplift of the chain which generally shows an ''out-ofsequence'' character. Recent studies have confirmed this interpretative scheme also for the central-northern portions of the Apennines (Basili et al 2008;Montone et al 2004;Scrocca et al 2007;Carminati et al 2010b). The accretion occurs at the expenses of the upper layers of the lower plate.…”
Section: Northeastern Apennines Frontmentioning
confidence: 56%
“…4). In fact the Cremona salient propagated into the Lombard Graben-basin to the north; the Parma recess developed at the encroachment with the Trento Horst, whereas the Ferrara salient or arc occurs along the southern propagation of the Belluno Graben (Carminati et al 2010b). This is a tectonic terminology, since we are defining horst and gaben as controlling thickness variations, rather than lateral facies (e.g., Trento Platform and Belluno Basin).…”
mentioning
confidence: 95%